Breeding Preference and Bionomics of Anopheles spp. at the Malarial Endemic Area, Runut Village, East Nusa Tenggara Province, Indonesia - Gery Morsales Munthe; David Nugraha; Gabriel Pedro Mudjianto; Etik Ainun Rohmah; Arnoldina Dolfina Dua Weni; Zukhaila Salma; Lynda Rossyanti; Fitriah; Suhintam Pusarawati; Budi Utomo; ukmawati Basuki; Haruki Uemura (Biomolecular and Health Science Journal, 2022)
Introduction: Anopheles mosquito is transmitting malaria, one of the health problems in Indonesia. Understanding Anopheles mosquito behaviour and its breeding preference is one of the crucial keys to prevent malaria transmission. This study aimed to identify the breeding place distribution and bionomics of Anopheles spp. in Runut village, Sikka district, East Nusa Tenggara. Methods: A descriptive observational study was conducted in Runut village, Waigete sub- district, in April 2018. Anopheles spp. larvae were collected in 7 suspected breeding places consisting of 2 rice fields, 3 fish ponds, and 2 puddles. Mosquitos behaviour was observed using bed-net traps located inside and outside the house from 7.15 PM to 1.15 AM after obtaining informed consent. Mosquito collection using bed-net trap were performed for 40 minutes then followed by resting mosquito collection for 10 minutes. Results: Anopheles spp. larvae were found in most of the suspected aquatic habitats, presenting different densities and together with larvae of the other mosquito species. Relatively high number of Anopheles spp. larvae was obtained from a puddle. Only one female mosquito of Anopheles spp. resting on the wall inside house was found around 00.55 – 01.05 AM and resulted in low mosquito density determination. Conclusion: Anopheles spp. larvae were harbouring in most of the aquatic habitats and one puddle contained moderately abundant larvae of Anopheles in Runut village, Sikka district, East Nusa Tenggara, Indonesia. Even only one Anopheles spp. mosquito was detected inside the house, residents in Runut village should regular use insecticide-treated bed nets and continuous observation of mosquito breeding places especially puddles to prevent malaria and other mosquito-borne diseases.